Starvation Stress Causes Body Color Change and Pigment Degradation in Acyrthosiphon pisum - Wang, Xing-Xing; Chen, Zhan-Sheng; Feng, Zhu-Jun; Zhu, Jing-Yun; Zhang, Yi; Liu, Tong-Xian (Frontiers in Physiology, 2019)
The pea aphid, Acyrthosiphon pisum (Harris), shows body color shifting from red to pale under starvation in laboratory conditions. These body color changes reflect aphid’s adaptation to environmental stress. To understand the color-shifting patterns, the underlying mechanism and its biological or ecological functions, we measured the process of A. pisum’s body color shifting patterns using a digital imagery and analysis system; we conducted a series of biochemical experiments to determine the mechanism that causes color change and performed biochemical and molecular analyses of the energy reserves during the color shifting process. We found that the red morph of A. pisum could shift their body color to pale red, when starved; this change occurred rapidly at a certain stress threshold. Once A. pisum initiated the process, the shifting could not be stopped or reversed even after food was re-introduced. We also discovered that the orange-red pigments may be responsible for the color shift and that the shift might be caused by the degradation of these pigments. The carbohydrate and lipid content correlated to the fading of color in red A. pisum. A comparative analysis revealed that these reddish pigments might be used as backup energy. The fading of color reflects a reorganization of the energy reserves under nutritional stress in A. pisum; surprisingly, aphids with different body colors exhibit diverse strategies for storage and consumption of energy reserves.